2019
DOI: 10.1038/s41598-019-52195-5
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus and human telomerase RNA component gene in cervical cancer progression

Abstract: This study aimed to examine hTERC gene in different grades of cervical intraepithelial neoplasia (CIN) and cervical cancer, and the association between hTERC and high risk-human papillomavirus (HR-HPV) infection. Patients who underwent cervical cancer screening at the Second Affiliated Hospital of Kunming Medical University between October 2010 and December 2011 were enrolled. All patients underwent liquid-based cytology test and hybrid capture 2 (HC2) for HPV detection. hTERC was examined using fluorescence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Telomerase is a ribonucleoprotein enzyme complex that adds 50-TTAGGG-30 repeats to the chromosomal ends known as telomeres, which play an important part in maintaining chromosomal stability during DNA replication [ 21 , 23 , 24 ]. Human telomerase consists of three subunits: one RNA component (hTERC), which functions as a template for DNA replication; one of unknown function (TP1) and the human telomerase reverse transcriptase (hTERT) [ 95 , 96 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Telomerase is a ribonucleoprotein enzyme complex that adds 50-TTAGGG-30 repeats to the chromosomal ends known as telomeres, which play an important part in maintaining chromosomal stability during DNA replication [ 21 , 23 , 24 ]. Human telomerase consists of three subunits: one RNA component (hTERC), which functions as a template for DNA replication; one of unknown function (TP1) and the human telomerase reverse transcriptase (hTERT) [ 95 , 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the E6/E7 oncogene encoding the HPV proto-oncoprotein can up-regulate telomerase activity by human telomerase RNA component (hTERC) gene amplification. Studies have shown an important correlation between HR-HPV infection and hTERC up-regulation in CC progression [ 23 , 24 , 25 , 26 ]. Telomerase activity as a prognostic biomarker in CC has been demonstrated through numerous studies and it is generally recommended as an ancillary biomarker in CC screening, after cytology and HPV DNA detection.…”
Section: Introductionmentioning
confidence: 99%
“…At a global level, cervical cancer is one of the most common malignant forms of cancers among women [11]. In recent years, resistant to chemotherapeutics and increasing toxicity of the drugs have been observed that have decreased the efficiency of the existing treatment strategies for cervical cancer [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…According to the 2020 Global Cancer Statistics, CC ranks fourth in morbidity and mortality among women with cancer whereby there were 604,127 new cases and 41,831 deaths in the year ( 3 ). The highest global prevalence of CC occurs in developing countries (87%), of which it is the foremost form of gynecological cancer ( 4 ) whereas China accounts for 12% of the global incidence of CC and 11% of deaths ( 5 ). The CC screening program aims to reduce the incidence and mortality of the cancer ( 6 ).…”
Section: Introductionmentioning
confidence: 99%